ANALISA PELAYANAN JASA PEMAKAIAN GARBARATA TERHADAP KEPUASAN MASKAPAI PENERBANGAN DI BANDAR UDARA INTERNASIONAL SOEKARNO – HATTA ANALYSIS OF AVIOBRIDGE USAGE SERVICES TO AIRLINES SATISFACTION AT SOEKARNO-HATTA INTERNATIONAL AIRPORT - Ariyono Setiawan; Aizatul Mufidah; Lady Silk Moonlight (Approach : Jurnal Teknologi Penerbangan, 2019)
Airport services are services provided to airport service users by airport operators. The airport business is divided into the Aeronautical Services and Non-Aeronautical Services businesses. Aeronautical Services is a field that deals directly with aviation activities, including Landing Placement and Storage Services (PJP4U), Aircraft Passenger Services (PJP2U), Aviobridge Use Services (Aviobridge), Counter Use Services (Check-In Services) Counter). Aviobridge Usage Services is one of the major revenues and these services are needed because the function of Aviobridge is to facilitate passenger access from the terminal to the aircraft or vice versa.The commercial unit that handles the Aeronautics business in the Aviobridge usage service must input the docking/undocking time data from the Aviobridge Utilization Sheet recorded by the Aviobridge operator into the Operating & Services Data System (OASys) application. Furthermore, it is calculated by the rate based on the aircraft's Maximum Take-Off Weight (MTOW) weight limitation, the number of Aviobridge used and the length of use. From these results, the airline or the transport company that uses the service of using Aviobridge pays the amount of the cost bill by the results of the calculation. The charge bill is still experiencing inequality between the time of Aviobridge usage recorded on the system with the Aviobridge Utilization Sheet so that the usage time is not appropriate and the MTOW limitation of planes using Aviobridge is updated late to the company PT. Angkasa Pura II and caused the airlines to complain. This study aims to determine the service usage of Aviobridge for airlines and provide solutions to avoid complaints about the inequality of fees paid by airlines so that these services provide satisfaction and trust for service users. Data obtained from direct observation, questionnaires and literature studies. For the method of analysis using quantitative descriptive methods.